Blood transfusion and ischaemic outcomes according to anemia and bleeding in patients with non-ST-segment elevation acute coronary syndromes: Insights from the TAO randomized clinical trial. (1st November 2020) - Deharo, P.; Ducrocq, G.; Bode, C.; Cohen, M.; Cuisset, T.; Mehta, S.R.; Pollack, C.V.; Wiviott, S.D.; Rao, S.V.; Jukema, J.W.; Erglis, A.; Moccetti, T.; et al.
Abstract: Background: The benefits and risks of blood transfusion in patients with acute myocardial infarction who are anemic or who experience bleeding are debated. We sought to study the association between blood transfusion and ischemic outcomes according to haemoglobin nadir and bleeding status in patients with NST-elevation myocardial infarction (NSTEMI). Methods: The TAO trial randomized patients with NSTEMI and coronary angiogram scheduled within 72h to heparin plus eptifibatide versus otamixaban. After exclusion of patients who underwent coronary artery bypass surgery, patients were categorized according to transfusion status considering transfusion as a time-varying covariate. The primary ischemic outcome was the composite of all-cause death or MI within 180 days of randomization. Subgroup analyses were performed according to pre-transfusion hemoglobin nadir and bleeding status. Results: 12, 547 patients were enrolled. Among these, blood transfusion was used in 489 (3.9%) patients. Patients who received transfusion had a higher rate of death or MI (29.9% vs. 8.1%, p<0.01). This excess risk persisted after adjustment on GRACE score and nadir of hemoglobin (HR 3.36 95%CI 2.63-4.29 p<0.01). Subgroup analyses showed that blood transfusion was associated with a higher risk in patients without overt bleeding (adjusted HR 6.25 vs. 2.85; p-interaction 0.001) as well as in those with hemoglobin nadir > 9.0 g/dl (HR 4.01; p-interaction<0.0001). Conclusion: In patients with NSTEMI, blood transfusion was associated with an overall increased risk of ischaemic events. However, this was mainly driven by patients without overt bleeding and those hemoglobin nadir > 9.0g/dl. This suggests possible harm of transfusion in those groups. Highlights: Blood transfusion was associated with increased risks of death and MI after a NSTEMI. This increase in ischemic events was mainly driven by patients transfused without overt bleeding. An increase in ischemic risk was also observed in patients with hemoglobin nadir > 9.0 g/dl.